The virtual chemistry lab (VC-L): virtual reality as a learning tool for Malaysia's secondary school - Romli, R.; Shiratuddin, Mohd Fairuz; Hashim, S. (Universiti Utara Malaysia, 2003)
Virtual Reality (VR) and its related technologies have paved the way to new opportunities that can be applied to improve current practices and processes in varieties of fields, including education. This research paper presents the `Virtual Chemistry Lab’ (VC-L). The motivation of the research was based on the current challenges faced by students to learn and understand, and also educators to teach chemistry using conventional and traditional means. The VC-L proposes a new method to assist current teaching practices. In supporting the VC-L proposal, issues such as cost, materials and time were among the elements studied and taken into consideration. The steps engaged to accomplish the research objectives were; elementary research methodologies, preliminary studies that primarily concentrated on gathering information, prototype software application design and development, information analysis and documentation. The WildTangent Web Driver and Autodesk 3D Studio MAX were the software development tools used to design and develop the prototype application.